SISTEM PENUNJANG KEPUTUSAN PEKERJA TERBAIK PADA PT. DWI KARYA BUMI MANDIRI DENGAN METODE SIMPLE ADDITIVE WEIGHTING - Rizky Eka Putra; Jap Tji Beng; Desi Arisandi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2020)
Workers are an important asset in a company. PT. Dwi Karya Bumi Mandiri does not yet have a system that can determine the best workers and still uses manual methods. The purpose of this research is to create a program that can determine the best workers at PT. Dwi Karya Bumi Mandiri. Decision Support System is used along with Simple Additive Weighting (SAW) as the method. The SAW method is used to determine the best workers at PT. Dwi Karya Bumi Mandiri. Based on the results of testing that have been conducted it can be concluded that the program can help the foreman and the owner of the company in determining the best workers at PT. Dwi Karya Bumi Mandiri.